Traditional Knowledge on Tree Management and Forest Restoration of Mabira Central Reserve, Uganda - Mulugo, L.W.; Nabanoga, G.N.; Turyahabwe, N.; Eilu, G.; Galabuzi, C.; Tabuti, J.R.S; Kakudidi, E.; Sibelet, N. (2nd World Agroforestry Congress, 2009)
Tropical forest degradation and loss has escalated worldwide and Mabira forest is not exceptional ( Figure 1). Efforts are needed to reverse this situation by combining traditional forest management with new innovative approaches. This study was undertaken to identify appropriate forest restoration measures based on traditional forest restoration and tree management practices of local people around Mabira Forest Reserve (MFR).